2022
DOI: 10.1002/jgt.22801
|View full text |Cite
|
Sign up to set email alerts
|

Maximum spectral radius of outerplanar 3‐uniform hypergraphs

Abstract: In this paper, we study the maximum spectral radius of outerplanar 3‐uniform hypergraphs. Given a hypergraph MJX-tex-caligraphicnormalℋ ${\rm{ {\mathcal H} }}$, the shadow of MJX-tex-caligraphicnormalℋ ${\rm{ {\mathcal H} }}$ is a graph G $G$ with V ( G ) = V ( ℋ ) $V(G)=V({\rm{ {\mathcal H} }})$ and E ( G ) = { u v : u v ∈ h for some h ∈ E ( MJX-tex-caligraphicscriptH ) } $E(G)=\{uv:uv\in \,h\,\text{for\unicode{x02007}some}\,h\in E({\mathscr{H}})\}$. A graph is outerplanar if it can be embedded in the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…They also obtained a p-spectral version of the Erdős-Ko-Rado theorem on t-intersecting r-graphs. Recently, Ellingham, Lu and Wang [4] showed that the n-vertex outerplanar 3-graph of maximum spectral radius is the unique 3-graph whose shadow graph is the join of an isolated vertex and the path P n−1 . Gao, Chang and Hou [9] studied the spectral extremal problem for K + r+1 -free r-graphs among linear hypergraphs, where K + r+1 is the r-expansion of the complete graph K r+1 , i.e., K + r+1 is obtained from K r+1 by enlarging each edge of K r+1 with (r − 2) new vertices disjoint from V (K r+1 ) such that distinct edges of K r+1 are enlarged by distinct vertices.…”
Section: Introductionmentioning
confidence: 99%
“…They also obtained a p-spectral version of the Erdős-Ko-Rado theorem on t-intersecting r-graphs. Recently, Ellingham, Lu and Wang [4] showed that the n-vertex outerplanar 3-graph of maximum spectral radius is the unique 3-graph whose shadow graph is the join of an isolated vertex and the path P n−1 . Gao, Chang and Hou [9] studied the spectral extremal problem for K + r+1 -free r-graphs among linear hypergraphs, where K + r+1 is the r-expansion of the complete graph K r+1 , i.e., K + r+1 is obtained from K r+1 by enlarging each edge of K r+1 with (r − 2) new vertices disjoint from V (K r+1 ) such that distinct edges of K r+1 are enlarged by distinct vertices.…”
Section: Introductionmentioning
confidence: 99%
“…There has been extensive research on finding the maximum spectral radius (i.e. the largest eigenvalue) of planar and outerplanar (hyper)graphs and the corresponding extremal (hyper)graphs; see, for example, [3,6,7,9,11,32,17,19,21,28,29,30,31,10]. In [13], Gotshall, O'Brien and Tait studied the maximum spread of outerplanar graphs and narrowed down the structure of the extremal graph attaining the maximum spread.…”
Section: Introductionmentioning
confidence: 99%